(untitled) - Desai, Mihir A. (Boston, Massachusetts, 2019)
If you're not a numbers person, then balance sheets and financial jargon can be intimidating and easy to ignore. But if you want to advance in your career, it's crucial that you are able to make smart financial decisions and develop the confidence to clearly communicate those decisions to others. In How Finance Works, Mihir Desai--a professor at Harvard Business School and author of the widely praised book The Wisdom of Finance--guides you into the complex but endlessly fascinating world of finance and demystifies it in the process. Through entertaining stories, interactive exercises, full-color visuals, and a conversational style that belies the topic, Desai tackles a broad range of subjects that will give you the skills and knowledge you need to finally understand how finance works. These include: The ins and outs of balance sheets, and how different financial levers can affect a company's performance How companies fund their operations and investments in different ways Why finance is concerned with cash flow versus profits How value is created, measured, and maximized The importance of capital markets in helping companies grow Whether you're a student or manager, an aspiring CFO or entrepreneur, How Finance Works is the colorful and interactive guide you need to help you start thinking more deeply about the numbers.
Keywords: Doanh nghiệp kinh doanh,Business enterprises; Tài chính,Finance